Exclusive Breastfeeding and Its Determinants in Yaoundé, Cameroon: A Retrospective Survival Analysis - Gloria Akah Ndum Okwen; Esron Daniel Karimuribo; Helena Aminiel Ngowi; Edith Nig Fombang (Journal of Pregnancy)
Exclusive breastfeeding (EBF) of infants for the first six months of life is a global public health goal that is linked to the reduction of morbidity and mortality in infants, especially in low middle-income countries. In low middle-income countries like Cameroon, it is realistic that compliance with EBF can significantly reduce the burden of under five mortality rate. The purpose of this study was to assess adherence and determinants influencing the duration of exclusive breastfeeding in Yaoundé, Cameroon. Data was collected through a mixed method and systematically through a retrospective survival analysis approach where a total number of 503 randomly selected individuals in Yaoundé, Cameroon, participated in the study. Data was collected between November 2019 and May 2020. A Cox proportional hazard modelling and Kaplan-Meier analysis were employed to identify prognostic factors affecting survival time defined as the duration, in months, from birth until the time of stopping EBF. The average time for nursing mothers to practice EBF was 3.61 ± 0.010 months. This study found that more than 90% of mothers were aware of the importance of compliance with EBF but only 38% practiced EBF and 62% of mothers could not adhere to EBF recommendations. Factors that influence compliance with EBF included a mother being married (HR: 0.70; 95% CI = [0.55-0.89], P =0.003) which was a protective factor while mother’s tertiary education (HR: 1.43; 95% CI = [1.11-1.84], P =0.005) was a risk factor with non-compliance with EBF when compared to those with basic or no formal education. The Kaplan-Meier curve indicated that as time goes on, babies are less likely to be exclusively breastfed after a specific time period within two and three months. This implies that the chance for a baby to remain exclusively breastfed after five months is 74.3% (0.74). Continuous sensitization and enforcement measures are recommended to promote EBF.